2010
DOI: 10.1186/1749-799x-5-37
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of bone formation by the osteoblast-specific transcription factor Osx

Abstract: Bone formation is a complex developmental process involving the differentiation of mesenchymal stem cells to osteoblasts. Osteoblast differentiation occurs through a multi-step molecular pathway regulated by different transcription factors and signaling proteins. Osx (also known as Sp7) is the only osteoblast-specific transcriptional factor identified so far which is required for osteoblast differentiation and bone formation. Osx knock-out mice lack bone completely and cartilage is normal. This opens a new win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
152
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(161 citation statements)
references
References 36 publications
7
152
0
2
Order By: Relevance
“…Thus, dosing, temporal, and spatial parameters of RNAi must be finely tuned. Temporally, Runx2 and Osx expression have been determined to peak within the first 72 hours after BMP stimulation [44]; furthermore, Runx2 expression is antecedent to Osx [69]. Thus, our RNAi treatments were engineered to deliver Runx2 siRNA 24 hours before and Osx siRNA simultaneously to rhBMP-2 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dosing, temporal, and spatial parameters of RNAi must be finely tuned. Temporally, Runx2 and Osx expression have been determined to peak within the first 72 hours after BMP stimulation [44]; furthermore, Runx2 expression is antecedent to Osx [69]. Thus, our RNAi treatments were engineered to deliver Runx2 siRNA 24 hours before and Osx siRNA simultaneously to rhBMP-2 administration.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SOX9, SP7, RUNX2, TWIST1 and IHH was tested because these molecules serve as regulators of normal skeletal development and control lineagespecific tumor differentiation. [13][14][15][16][17] Unlike cDNA expression profiling, which reports the pooled molecular signature of all cells within a tumor, immunohistochemical profiling reveals the intratumoral distribution of protein expression, an advantage in polymorphic cellular populations.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms are complex and include combinatorial interactions of multiple molecules promoting osteoblast and chondrocyte differentiation. [13][14][15][16][17] Nevertheless, studies suggest that the signal transduction molecule Indian hedgehog (IHH), and the transcription factors SP7 (also known as osterix, OSX), sex-determining region Y-box 9 (SOX9), runt-related transcription factor 2 (RUNX2, also known as CBFA1) and TWIST1 regulate the differentiation of osteogenic and chondrogenic cells from mesenchymal precursors. 13,[18][19][20][21] Furthermore, the aberrant function of these same molecules has also been implicated in the pathogenesis of some bone tumors including osteosarcoma and giant cell tumor.…”
mentioning
confidence: 99%
“…6 Osterix (OSX) is essential for the differentiation of preosteoblasts into mature osteoblasts, and one study showed that it might be stimulated by estrogen. 7 OSX is also expressed in osteoblasts 8 and cementoblasts.…”
Section: Introductionmentioning
confidence: 99%